Between Scylla and Charybdis: END and Its Attempt to Overcome the Bipolar World Order in the 1980s. (1st November 2016) - Berger, Stefan; LaPorte, Norman
Abstract : This article deals with European Nuclear Disarmament's (END) difficult positioning in the Cold War of the 1980s. Its vision was for a humanistic socialism from below that would be capable of breaking up the Cold War and unite a divided Europe that in turn could act as a possible "third way" between the liberal capitalism of the USA and the orthodox Communism of the Soviet Union. However, it proved difficult to build these alliances across the Cold War divide without talking, at the same time, to representatives of the "official" peace movements of the Communist states. END found itself between the Scylla of having no dialogue at all with Eastern Europe or the Charybdis of having a dialogue also with the Communist regimes which was seen sceptically by the dissidents. The article traces the difficulties of END of building humanistic socialist alliances for peace from below with special reference to END's Working Group on Germany.